Instructional Supervision Competencies Level of Public School Heads and Teacher Performance Outcomes - De Jesus, Marigold (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between Public School Heads’ Instructional Supervision Competencies under Domain 3 of the Philippine Professional Standards for School Heads (PPSSH) and teacher performance at Masbate National Comprehensive High School. Utilizing a descriptive research design with validated surveys, the study analyzed thirty highly qualified, mid-career educators and administrators, most of whom possess advanced graduate units or master's degrees. The findings revealed that school heads are "Highly Competent" across all Domain 3 strands, demonstrating particular strength in data-driven instructional feedback (M = 4.53) and curriculum alignment (M = 4.40). Correspondingly, teacher performance outcomes measured via the Results-Based Performance Management System (RPMS) were rated as "Outstanding," excelsior in curriculum planning (M = 4.34) and assessment monitoring (M = 4.53). Crucially, Multiple Linear Regression analysis identified Instructional Leadership (technical assistance and feedback) as the sole statistically significant predictor of teacher performance (β = .542, p = .001). This underscores that school heads succeed primarily when acting as instructional coaches rather than mere administrative managers. The study recommends enhancing school heads' clinical supervision and differentiated coaching skills, co-constructing feedback loops with teachers, and reinforcing peer-led Learning Action Cell (LAC) sessions to sustain outstanding pedagogical outcomes.
Keywords: Instructional leadership, Teacher performance, Technical assistance, Clinical supervision, School heads' competencies